Interação oral em língua espanhola: construção de uma proposta avaliativa - Soares, Franciane de Araújo (Brasil, 2020)
This research deals with the oral interaction evaluation, in the Spanish Language (SL) teaching-learning context. Faced with the difficulty to evaluate this communicative ability, we developed an evaluative proposal composed of three steps: the compilation of a Matriz of Descriptors for Oral Interaction Evaluation in Spanish Language.; the elaboration of a didactic activity focused on the oral interaction development in SL and the construction of a rubric that enables (self)assessment, based on criteria and descriptors related to oral communicative competence in the language. This proposal purpose is to contribute to the SL teaching-learning process, taking into account the evaluation process, based on the presential and virtual communicative context. To evaluate the proposal, we conducted a Case Study with students of an Intermediate Spanish Course, at the Language Center, at Federal Institute of Education, Science and Technology of Amazonas, Manaus Centro Campus. The methodological procedures used take into account the identification of students' needs and interests; the application and analysis of the contributions and limitations from the created proposal, based on the diagnostic data made by the students, regarding the activity and the instrument used, and the teacher's observations. The results indicate that the evaluation proposal contributed to the identification of students' proficiency levels, considering the evaluated criteria, besides it had provided a self-assessment moment of their own learning. From this research were developed two products, the first is a Matriz of Descriptors for Oral Interaction Evaluation in Spanish Language, composed by the compiled descriptors from the Common European Framework of Reference for Languages (CEFRL) and the main proficiency exams in SL: Diploma de Español como Lengua Extranjera (DELE), Certificado de Español: Lengua y Uso (CELU) Servicio Internacional de Evaluación de la Lengua Española (SIELE), as well as the language assessment parameters of the Association of Language Testers in Europe (ALTE), with suggestions for the evaluative activities elaboration. The second product is a Didactic Guide for Spanish teachers, with guidelines for the evaluation proposal use, which can serve as a model for the other proposals construction or be adapted to different evaluation formats.